Effects of propafenone on electrical and mechanical activities of single ventricular myocytes isolated from guinea-pig hearts. - Honjo, H. (1989)
1. The effects of propafenone on the transmembrane action potential and sarcomere shortening during twitch contraction were investigated in single ventricular myocytes isolated from guinea-pig hearts. 2. Propafenone at low concentrations (3-5 x 10(-7) M) slightly lengthened action potential duration (APD), but shortened it at higher concentrations. The shortening of APD was accompanied by an attenuation of sarcomere shortening during twitch contraction. 3. Propafenone (greater than 10(-6) M) caused a concentration-dependent decrease in the maximum upstroke velocity (Vmax) of the action potential. In the presence of propafenone (3 x 10(-6) M), trains of stimuli led to an exponential decline in Vmax. A time constant for the recovery of Vmax from the use-dependent block was 4.8 s. 4. In myocytes treated with propafenone (3 x 10(-6) M), the Vmax of test action potentials preceded by the conditioning clamp pulses to 0 mV was progressively decreased by increasing the duration of single clamp pulse or by increasing the number of multiple brief clamp pulses. 5. These findings suggest that propafenone has use-dependent inhibitory action on the sodium channel by binding to the channel during both activated and inactivated states, and that the unbinding rate is comparable to that of Class-I antiarrhythmic drugs with intermediate kinetics. Propafenone may also have an inhibitory action on calcium and potassium channels.